برنامج الانغماس اللغوي لتنمية مهارات اللغة العربية (دراسة حالة في جامعة دار السلام كونتور ) - Hani'atul Mabruroh; Muhammad Slamet; Eslam Marouf Sayyed Marouf (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The availability of human resources in various Islamic educational institutions and pesantren in Indonesia requires more intensive attention. The interest of prospective students each year indicates that pesantren and Islamic institutions in Indonesia are becoming increasingly popular among the community. Therefore, it is essential to prepare the best candidates to become skilled teachers capable of teaching Arabic. One strategic solution is to train these teacher candidates to participate in a self-development program focused on Arabic language skills. The purpose of this research is to describe the language immersion program of the Department of Arabic Language Education in Egypt. This research uses a qualitative descriptive method. Data were collected through field observations, interviews, and documentation, while data analysis employed the Miles and Huberman method, which includes data reduction, data presentation, and conclusion drawing. The results of this program indicate that immersion in an Arabic-speaking environment has a significant impact, despite the limited duration of the activities. Students have shown improvement in applying the four Arabic language skills compared to before the program.